Pandangan Hakim Terhadap Gugat Cerai Seorang Istri Dalam Keadaan Hamil - Qoidul Khoir (Universitas Sains dan Teknologi Komputer, 2019)
Marriage is a sacred bond between husband and wife with a firm agreement. A harmonious and lasting marriage is a goal that is highly desired by Islam. However, it cannot be denied that in a family there must be differences of opinion between family members, which in turn can cause division. It turns out that divorce also often occurs when the wife is pregnant, which has become a phenomenon today. As happened to a married couple where the wife sued her husband for divorce while pregnant to the Malang Religious Court with No.789/Pdt.G/2008/PA.Mlg. This is very contrary to Islamic law. Therefore, this research has objectives. Namely, to find out the opinion of the judges of the Religious Court of Malang city related to the case of divorce of a pregnant wife. As well as knowing the basis for consideration by the Panel of Judges in deciding case No. 789/Pdt.G/2007: 789/Pdt.G/2008/PA.Mlg. The research used a type of qualitative research. The data of this research was collected through interviews from informants and decision documents of the Malang Religious Court. While the analysis method in this study uses qualitative descriptive analysis techniques. A wife who wants a divorce from her husband then she must pay a ransom to her husband as compensation for the husband's love for her and file a divorce suit at the local Religious Court. The amount of iwadl is in accordance with the husband's request and the wife's willingness to pay it. If the husband does not wish to divorce his wife, based on the examination conducted during the trial, the judge has the right to decide the divorce between the husband and wife. However, in the Religious Courts there are rarely cases of pure Khulu' as described in Islamic law. In the Religious Court the divorce suit filed by the wife is known as Gugat Cerai.